Education on Healthy Household Practices in Efforts to Prevent Stunting : Case Study in Sidomulyo Village, Tanjungpinang - Indra Martias; Luh Pitriyanti; Risman Kurnia; Rinaldi Daswito; Hevi Horiza; Suci Yuliana Pratiwi (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Clean and healthy living behaviours (PHBS) are habits practised by individuals or families that enable them to take independent action on health issues and play an active role in health initiatives both within the family and in the community. PHBS can start with oneself and one's family through clean and healthy habits in daily life. The implementation of PHBS is also an important step in preventing various diseases in children, especially diseases that are difficult to prevent, one of which is stunting. The target audience for this outreach programme was housewives in Kampung Sidomulyo RT 002/RW 13. The outreach programme was conducted through presentations and discussions. Before the outreach programme was implemented, a pre-test questionnaire was administered to determine the level of knowledge about PHBS related to stunting. Then, outreach material on household PHBS and clean water was provided. Following the presentation of the material, a discussion session and post-test were conducted to assess the level of understanding of the material provided. The results of the respondents' knowledge before the PHBS counselling (pre-test) were 5.12%, and the results of the respondents' knowledge after the PHBS counselling (post-test) were 5.94%. Socialisation of PHBS to housewives has been proven to increase their knowledge about the importance of implementing clean and healthy living behaviours in the household environment. This increased understanding plays an important role in encouraging the adoption of daily healthy habits, which not only maintain family hygiene and health, but also serve as a strategic step in preventing stunting in children. With better knowledge, housewives can play an active role as the main drivers of family and community health.